Pengaruh Capital Adequacy Ratio (CAR), Loans Deposit Ratio (LDR) dan Return On Asset (ROA) Terhadap Laba Bersih Pada PT. Bank Central Asia (BCA) Tbk Periode 2008-2017 - Anita Nasution (Universitas Batanghari Jambi, 2019)
Thepurpose of this research is to know the influence of the capital adequacy ratio (CAR), loan to deposit ratio (LDR) and return on assets (ROA) simultaneously and partial against net profit at PT Bank Central Asia Tbk priode 2008-2017. This research is a desciptive quantitative research and analysis tool used in this research are multiple linear regression is useful to see the direction of the relationship between the variable bound against free. For the purpose of answering the number one used statistical test i.e test F and to answer the purpose number 2 used statistical test i.e test t. The correlation coefficient to know how the relationship between variables and coefficients of determination of useful to see the magnitude of the influence of the variable bound against free. PT. Bank Central Asia is one of the largest and most famous banking in Indonesia and banking has a positive profit value on each year. Based on the customer satisfaction index of commercial banks released by the info bank consistently from year sebelunya, Bank Central Asia (BCA) are on top-tier commercial banks that provide the customer satisfaction. Result SPSS 20 get a multiple linear regression equation is Y = 0,142 – 0,484 X1 + 3,034 X2 + 1,524 X3 + e. The determination is 0,904, meaning that is a CAR (X1), LDR (X2) and ROA (X3) of net profit (Y) at on PT Bank Central Asia Tbk priode 2008-2017.From the result of the obtained values SPSS (coefficient) r2 this figure amounted 0,818 states that the CAR,LDR and ROA against is able to explain the variabel net profit by 81,8% and the reaining 18,1% is explained by other factors which is not included in the research model. For companies based on this research should more companies encourage variable that could affect profits at PT Bank Central Asia Tbk (BCA) and for the next researcher is expected to try other financial ratios as variables independent, because it is very possible other financial ratio effect on net income.